2009
DOI: 10.1111/j.1551-2916.2009.02966.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Transport in Off‐Stoichiometric Uranium Dioxide by Atomic Level Simulation

Abstract: The thermal conductivity of hypo-and hyperstoichiometric UO 2 is calculated as a function of defect concentration and temperature using the direct method in molecular dynamics simulations. Anion defects, the dominant defects in UO 2 , are shown to significantly influence the thermal conductivity. Lattice dynamics calculations show how this reduction arises from changes in the nature of the lattice vibrations, as characterized by the polarization vectors and participation ratios. In addition, 235 U isotopic def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…14 The typical grain size of UO 2 in pristine nuclear reactor fuel is ~20 mm; by contrast MD simulations indicated that there is only a significant effect on the thermal conductivity for grain sizes of ~600 nm or less. 14 However, this study did not address the issue of the effects of grain boundary segregation on thermal transport which could be significant.…”
Section: Our Previous MD Simulations Havementioning
confidence: 97%
See 1 more Smart Citation
“…14 The typical grain size of UO 2 in pristine nuclear reactor fuel is ~20 mm; by contrast MD simulations indicated that there is only a significant effect on the thermal conductivity for grain sizes of ~600 nm or less. 14 However, this study did not address the issue of the effects of grain boundary segregation on thermal transport which could be significant.…”
Section: Our Previous MD Simulations Havementioning
confidence: 97%
“…12 They showed that all of these potentials are limited to some degree or another in the fidelity with which they reproduce the physical properties of UO 2 . The thermaltransport properties as described by one such potential, that of Busker et al, 13,14 has been examined in detail. This potential was chosen because it is also parameterized for hypo-and hyperstoichiometric UO 2 , which most of the other potentials were not.…”
Section: Thermal Transport: Microstructure Scalementioning
confidence: 99%
“…41 While these irradiation conditions do not necessarily reflect the reactor conditions, they were tailored to capture relevant physical mechanisms important for validation of thermal transport models. 43,44 It should be noted that the original intention was to study all of these conditions in UO 2 , but has not yet been accomplished due to difficulties that was encountered in performing ion irradiations on UO 2 over a broad range of temperatures and ion fluences that produced samples suitable for TR measurements.…”
Section: Measurements In Ion Irradiated Materialsmentioning
confidence: 99%
“…19 In addition to the fission gases, the effect of nonstoichiometry and Frenkel pairs on thermal conductivity is also important. 43,69 These types of defects may exist under the presence of radiation flux and are absent in standard post irradiation examination.…”
Section: Importance Of Irradiation Damage On Thermal Conductivitymentioning
confidence: 99%
“…Several examples have been published recently. Molecular dynamics computations were applied for extracting the thermal expansion and thermal conductivity of un-irradiated UO2 fuel and implementing the correlation in the FRAPCON code [1]. A similar molecular dynamics analysis was carried out to simulate the interaction of a He or Xe filled bubble with a fission fragment [2], or empirical potential simulations were applied in order to predict swelling due to soluble solid fission in a fuel performance code [3].…”
Section: Introductionmentioning
confidence: 99%